A social enterprise approach to empowering micro, small and medium enterprises (SMEs) in Indonesia - Irfan Ridwan Maksum; Amy Yayuk Sri Rahayu; Dhian Kusumawardhani (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Micro-enterprises play a critical role in the Indonesian economy, in which they supply 99.8% of the country's employment and account for more than 95% of all enterprises in Indonesia. However, these firms experience many impediments, including a lack of capital, skills, and technology, which creates poor competitiveness. Although the Indonesian government has implemented many policies to deal with these problems, none have been adequate in improving the capacity and productivity of micro, small, and medium enterprises (SMEs). The empowerment program "Iptekda LIPI-Penerapan dan Pemanfaatan Ilmu Pengetahuan dan Teknologi di Daerah Lembaga Ilmu Pengetahuan Indonesia (LIPI)-The Technology for Region Program of the Indonesian Institute of Sciences" proposed a new approach using a social enterprise to solve this issue. This paper analyses the social-enterprise approach of Iptekda LIPI which incorporates market and social welfare to determine the problems experienced by SMEs. The researchers conducted in-depth interviews with the owners of SMEs in West and East Java to explore how this approach may contribute to their businesses and to analyze the challenges of the social enterprise approach in empowering SMEs.
Keywords: 650; micro-enterprise empowerment; social enterprise policy; technology for regions program